2008
DOI: 10.2196/jmir.1005
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Smoking Cessation Program Delivered Through Internet and Cell Phone Without Nicotine Replacement (Happy Ending): Randomized Controlled Trial

Abstract: Background Happy Ending (HE) is an intense 1-year smoking cessation program delivered via the Internet and cell phone. HE consists of more than 400 contacts by email, Web pages, interactive voice response, and short message service technology. HE includes a craving helpline and a relapse prevention system, providing just-in-time therapy. All the components of the program are fully automated.Objective The objectives were to describe the rationale for the design of HE, to assess the 12-month efficacy of HE in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 30 publications
(48 reference statements)
0
178
0
Order By: Relevance
“…Five studies were randomized trials that compared two interventions, one of which was intended to act as an active control (Abroms, Windsor, & Simons-Morton, 2008;Brendryen, Drozd, & Kraft, 2008;Japuntich et al, 2006;King et al, 2009;Mermelstein & Turner, 2006). Two studies included treatment users who selfselected to participate in a research evaluation with no comparison or control group (Hotta et al, 2007;Zbikowski, Hapgood, Smucker Barnwell, & McAfee, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were randomized trials that compared two interventions, one of which was intended to act as an active control (Abroms, Windsor, & Simons-Morton, 2008;Brendryen, Drozd, & Kraft, 2008;Japuntich et al, 2006;King et al, 2009;Mermelstein & Turner, 2006). Two studies included treatment users who selfselected to participate in a research evaluation with no comparison or control group (Hotta et al, 2007;Zbikowski, Hapgood, Smucker Barnwell, & McAfee, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the studies evaluated programs specifically for tobacco cessation (Abroms et al, 2008;Brendryen et al, 2008;Japuntich et al, 2006;Hotta et al, 2007;Mermelstein & Turner, 2006;Woodruff et al, 2007;Zbikowski et al, 2008), with one study examining Internet treatment for problem and pathological gamblers (Carlbring & Smit, 2008) and one for substance abuse (King et al, 2009). The target population was primarily treatment-seeking adults, although three papers evaluated programs developed specifically for adolescents or young adults (Abroms et al, 2008;Mermelstein & Turner, 2006;Woodruff et al, 2007) and one targeted university employees (Hotta et al, 2007).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane review, however, showed inconsistent results 10. Recently, internet‐based interventions have been shown to be effective for smoking cessation 15, 16. Many effective internet‐based interventions in the Netherlands were individually computer‐tailored interventions, where health messages are tailored to input provided by the smokers via questionnaires 10, 15, 17.…”
Section: Introductionmentioning
confidence: 99%